2007
DOI: 10.1002/ijc.23309
|View full text |Cite
|
Sign up to set email alerts
|

Fra‐1 regulates vimentin during Ha‐RAS‐induced epithelial mesenchymal transition in human colon carcinoma cells

Abstract: The process of epithelial mesenchymal transition, whereby cells acquire molecular alterations and fibroblastic features, is a fundamental process of embryogenesis and cancer invasion/metastasis. The mechanisms responsible for epithelial mesenchymal transition remain elusive. Human tumors frequently establish constitutively activated RAS signaling, which contributes to the malignant phenotype. In an effort to dissect distinct RAS isoform specific functions, we previously established human colon cell lines stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 35 publications
5
60
0
3
Order By: Relevance
“…The presence of TBP-1 in Fra-1 complexes may thus facilitate their rapid turnover, providing a dynamic mechanism to regulate AP-1 activity. However, our chromatin immunoprecipitation analysis of the Fra-1 target gene VIM (Andreolas et al, 2008) found that only Fra-1 but not TBP-1 was present at the AP-1 site in the VIM gene promoter (Supplementary Figure 1). These findings indicate that TBP-1 is not a component chromatin-bound Fra-1 complexes.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of TBP-1 in Fra-1 complexes may thus facilitate their rapid turnover, providing a dynamic mechanism to regulate AP-1 activity. However, our chromatin immunoprecipitation analysis of the Fra-1 target gene VIM (Andreolas et al, 2008) found that only Fra-1 but not TBP-1 was present at the AP-1 site in the VIM gene promoter (Supplementary Figure 1). These findings indicate that TBP-1 is not a component chromatin-bound Fra-1 complexes.…”
Section: Discussionmentioning
confidence: 95%
“…Heterodimers of c-Fos and c-Jun, which are called AP-1, are transcription factors that regulate the expression of a wide variety of genes by binding to their promoters (Matsuo and Ray, 2004). One target of AP-1 is vimentin, which is transcriptionally up-regulated by AP-1 expression (Andreolas et al, 2008) and is involved in the EMT process following TWIST activation (Kang and Massague, 2004). Consistent with a possible role of FOS in metastasis, FOS protein is relatively highly expressed in HGC-27 cells, which display high metastatic capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the membrane portion was extracted using the mild frozen-defrozen technique, we could not detect any cell surface receptor protein including integrins. If the protein was indeed integrin, there is a possibility that the integrin was lost during protein extrac tion procedure since it has been reported that integrins can reside in detergent resistant membrane rafts 30) . Another possibility is the binding between integrin and NELL-1 was not strong enough to be detected by Far-Wes tern through the denaturing process by the reducing deter gent.…”
Section: Discussionmentioning
confidence: 99%